The Association of Axonal Damage Biomarkers and Osteopontin at Diagnosis Could Be Useful in Newly Diagnosed MS Patients - Eleonora Virgilio; Chiara Puricelli; Nausicaa Clemente; Valentina Ciampana; Ylenia Imperatore; Simona Perga; Sveva Stangalini; Elena Boggio; Alice Appiani; Casimiro Luca Gigliotti; Umberto Dianzani; Cristoforo Comi; et al. (Neurology International)
(1) Background: Multiple sclerosis (MS) is a biologically highly heterogeneous disease and has poor predictability at diagnosis. Moreover, robust data indicate that early disease activity strongly correlates with future disability. Therefore, there is a need for strong and reliable biomarkers from diagnosis to characterize and identify patients who require highly effective disease-modifying treatments (DMTs). Several biomarkers are promising, particularly neurofilament light chains (NFLs), but the relevance of others is less consolidated. (2) Methods: We evaluated a panel of axonal damage and inflammatory biomarkers in cerebrospinal fluid (CSF) and matched serum obtained from a cohort of 60 newly diagnosed MS patients. Disability at diagnosis, negative prognostic factors, and the initial DMT prescribed were carefully recorded. (3) Results: We observed correlations between different axonal biomarkers: CSF and serum NFL versus CSF total tau; and between the inflammatory marker osteopontin (OPN) and axonal biomarkers CSF p-Tau, CSF total tau, and serum NFL. CSF and serum NFL and total tau, as well as CSF OPN, positively correlated with EDSS at diagnosis. Moreover, CSF and serum NFL levels were increased in patients with gadolinium-enhancing lesions (p = 0.01 and p = 0.04, respectively) and in those treated with highly effective DMT (p = 0.049). Furthermore, CSF OPN and both CSF and serum NFL levels significantly differentiated patients based on EDSS, with a combined ROC AUC of 0.88. We calculated and internally validated biomarker (in particular serum NFL) thresholds that significantly identified patients with higher disability. Finally, CSF OPN levels and dissemination in the spinal cord were significant predictors of EDSS at diagnosis. (4) Conclusions: These preliminary exploratory data confirm the pathological interconnection between inflammation and axonal damage from early disease stages, contributing to early disability. Follow-up data, such as longitudinal disability scores, repeated serum measurements, a healthy control group, and external validation of our results, are needed. We suggest that combining several fluid biomarkers may improve the clinical characterization of patients.